Non-relativistic four dimensional p-brane supersymmetric theories and Lie algebra expansion. (1st June 2020) - Romano, Luca
Abstract: We apply the Lie algebra expansion method to the N = 1 super-Poincaré algerba in four dimensions. We define a set of p-brane projectors that induce a decomposition of the super-Poincaré algebra preparatory for the expansion. We show that starting from the N = 1 supergravity action in four dimensions it is possible to obtain non-relativistic supersymmetric theories, describing strings or membranes.